Measuring breathing induced oesophageal motion and its dosimetric impact. (August 2021) - Fechter, Tobias; Adebahr, Sonja; Grosu, Anca-Ligia; Baltas, Dimos
Highlights: By delineating the oesophagus on 3DCT large parts of the organ are missed. Oesophageal motion is heterogeneous across patients. Motion has a significant impact on the delivered dose. High motion amplitudes are not restricted to a specific part of the organ. Detailed motion model for the whole oesophagus. Abstract: Purpose: Stereotactic body radiation therapy allows for a precise dose delivery. Organ motion bears the risk of undetected high dose healthy tissue exposure. An organ very susceptible to high dose is the oesophagus. Its low contrast on CT and the oblong shape render motion estimation difficult. We tackle this issue by modern algorithms to measure oesophageal motion voxel-wise and estimate motion related dosimetric impacts. Methods: Oesophageal motion was measured using deformable image registration and 4DCT of 11 internal and 5 public datasets. Current clinical practice of contouring the organ on 3DCT was compared to timely resolved 4DCT contours. Dosimetric impacts of the motion were estimated by analysing the trajectory of each voxel in the 4D dose distribution. Finally an organ motion model for patient-wise comparisons was built. Results: Motion analysis showed mean absolute maximal motion amplitudes of 4.55 ± 1.81 mm left-right, 5.29 ± 2.67 mm anterior-posterior and 10.78 ± 5.30 mm superior-inferior. Motion between cohorts differed significantly. In around 50% of the cases the dosimetric passing criteria was violated. Contours created on 3DCT did not cover 14% of the organ for 50% of the respiratory cycle and were around 38% smaller than the union of all 4D contours. The motion model revealed that the maximal motion is not limited to the lower part of the organ. Our results showed motion amplitudes higher than most reported values in the literature and that motion is very heterogeneous across patients. Conclusions: Individual motion information should be considered in contouring and planning.